The Danish Atrial Fibrillation Registry: A Multidisciplinary National Pragmatic Initiative for Monitoring and Supporting Quality of Care Based on Data Retrieved from Administrative Registries - Frost L; Joensen AM; Dam-Schmidt U; Qvist I; Brinck M; Brandes A; Davidsen U; Pedersen OD; Damgaard D; Mølgaard I; Bedsted R; Damgaard Møller Schlünsen A; et al. (Clinical Epidemiology, 2023)
Lars Frost,1,2 Albert Marni Joensen,3 Ulla Dam-Schmidt,4 Ina Qvist,5 Margit Brinck,6 Axel Brandes,7,8 Ulla Davidsen,4 Ole Dyg Pedersen,9 Dorte Damgaard,10 Inge Mølgaard,11 Robert Bedsted,11 Anders Damgaard Møller Schlünsen,12 Miriam Grijota Chousa,12 Julie Andersen,12 Asger Roer Pedersen,1 Søren Paaske Johnsen,13 Nicklas Vinter1,13 1Diagnostic Centre, Silkeborg Regional Hospital, Silkeborg, Denmark; 2Department of Clinical Medicine, Aarhus University, Aarhus, Denmark; 3Department of Cardiology, North Denmark Regional Hospital, Hjørring, Denmark; 4Department of Cardiology, Bispebjerg Hospital, Copenhagen University Hospitals, Copenhagen, Denmark; 5Department of Cardiology, Aarhus University Hospital, Aarhus, Denmark; 6Department of Cardiology, Odense University Hospital, Odense, Denmark; 7Department of Cardiology, Esbjerg Hospital – University Hospital of Southern Denmark, Esbjerg, Denmark; 8Department of Regional Health Research, University of Southern Denmark, Odense, Denmark; 9Department of Cardiology, Zealand University Hospital, Roskilde, Denmark; 10Department of Neurology, Aarhus University Hospital, Aarhus, Denmark; 11Patient Representative, Aalborg and Roskilde, Denmark; 12The Danish Clinical Quality Program – National Clinical Registries (RKKP), Aarhus, Denmark; 13Danish Center for Health Services Research, Department of Clinical Medicine, Aalborg University, Aalborg, DenmarkCorrespondence: Lars Frost, Diagnostic Centre, University Clinic for Development of Innovative Patient Pathways, Silkeborg Regional Hospital; Department of Clinical Medicine, Aarhus University, Falkevej 3, Silkeborg, 8600, Denmark, Tel +45 23988590, Email larfrost@rm.dkAim: The Danish Atrial Fibrillation (AF) Registry monitors and supports improvement of quality of care for all AF patients in Denmark. This report describes the registry’s administrative and organizational structure, data sources, data flow, data analyses, annual reporting, and feedback between the registry, clinicians, and the administrative system. We also report the selection process of the quality indicators and the temporal trends in results from 2017– 2021.Methods and Results: The Danish AF Registry aims for complete registration and monitoring of care for all patients diagnosed with AF in Denmark. Administrative registries provide data on contacts to general practice, contacts to private cardiology practice, hospital contacts, medication prescriptions, updated vital status information, and biochemical test results. The Danish Stroke Registry provides information on stroke events. From 2017 to 2021, the proportion with a reported echocardiography among incident AF patients increased from 39.9% (95% CI: 39.3– 40.6) to 82.6% (95% CI: 82.1– 83.1). The initiation of oral anticoagulant therapy among patients with incident AF and a CHA2DS2-VASc score of ≥ 1 in men and ≥ 2 in women increased from 85.3% (95% CI: 84.6– 85.9) to 90.4% (95% CI: 89.9– 91.0). The 1-year and 2-year persistence increased from 85.2% (95% CI: 84.5– 85.9) to 88.7% (95% CI: 88.0– 89.3), and from 85.4% (95% CI: 84.7– 86.2) to 88.2% (95% CI: 87.5– 88.8), respectively. The 1-year risk of ischemic stroke among prevalent patients with AF decreased from 0.88% (95% CI: 0.83– 0.93) to 0.71% (95% CI: 0.66– 0.75). Variation in clinical performance between the five administrative Danish regions was reduced.Conclusion: Continuous nationwide monitoring of quality indicators for AF originating from administrative registries is feasible and supportive of improvements of quality of care.Keywords: atrial fibrillation, quality indicators, quality of care